MIMICRY AND HYBRIDITY THROUGH JAPANESE SOCIETY IN THE LAST SAMURAI MOVIE - Dikhy Zhawara; Satyawati Surya; Nasrullah Nasrullah (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2021)
This research aims to examine the mimicry and hybridity by Homi K. Bhabha in The Last Samurai movie. This research is also conducted to discuss more broadly how the characters develop themselves with western culture and create a new way of life. The forms of mimicry and hybridity represented by the Japanese characters in The Last Samurai movie are based on their practices in applying American culture where these practices are based on the desire to be more modern like the western countries. This research used a descriptive qualitative method to examine cultural adaptation by analyzing the context of the events in the story as well as how the characters deal with each event around them. The researcher revealed that the process of cultural adaptation could be seen through the way every individual responded toward west cultures in the environment. In The Last Samurai movie, the researcher found forms of mimicry and hybridity that the Japanese did for the sake of modernity focused on property, cloth, and language.